The Paraffin Cracking Reaction with NiMo/Active Natural Zeolite Catalyst: The Effect Temperature on Catalytic Activity - Khoirina Dwi Nugrahaningtyas; Eko Cahyono; Dian Maruto Widjonarko (ALCHEMY Jurnal Penelitian Kimia, 2015)
This research deals with the study of the paraffin cracking reaction with termal reaction, active natural zeolite (ZAA) and NiMo / active natural zeolite (ZAA) catalyst. Temperature variation was done in order to study the optimum temperature of paraffin cracking reactions. Paraffin cracking reaction carried out at temperatures of 200 - 400 °C and a hydrogen flow rate of 30 mL / min. Cracking products obtained, and then analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry(GCMS). Catalyst activity (%) was defined as the amount of lighter fractions/the amount of feed (paraffin) (%). The results showed that the catalyst NiMo/ZAA has the highest activity (31.33 %) at the cracking reaction temperature of 300 ºC